Pediatric Medial Discoid Meniscus: Case Series and Postoperative Outcomes - Franck Accadbled; Oliwer Sygacz; Joe Rassi; Alexandru Herdea (Children)
Discoid medial meniscus (DMM) is a rare congenital anomaly, with bilateral cases being even more uncommon. Due to its rarity, comprehensive data on its prevalence, clinical presentation, and optimal management strategies are limited. This study aimed to evaluate the prevalence, clinical characteristics, and treatment outcomes of symptomatic DMM in a pediatric population. A retrospective review was conducted on patients under 18 years of age diagnosed with symptomatic DMM. Data were extracted using ICD-10 codes Q68.6 and M23.16 and were supplemented by free-text searches. The inclusion criteria encompassed a confirmed DMM diagnosis, availability of MRI and radiographic imaging, complete clinical documentation, and a minimum of six months of postoperative follow-up. Demographic data, clinical presentations, imaging findings, surgical interventions, and outcomes were analyzed. Three patients (five knees) met the inclusion criteria. All presented with symptomatic DMM requiring surgical intervention. Arthroscopic saucerization combined with meniscal repair was performed in all cases. Postoperative follow-up revealed that two of the patients achieved excellent outcomes, while one required three reoperations due to retearing but remained symptom-free at one year post-revision. Radiographic assessments did not reveal characteristic changes typically associated with DMM. Symptomatic DMM, though rare, may be encountered more frequently than previously reported, especially when focusing on symptomatic cases. Arthroscopic saucerization with concurrent meniscal repair appears to be an effective treatment modality, yielding favorable mid-term outcomes. Given the limited number of cases and the variability in their presentations, further research with larger cohorts is essential to establish standardized management protocols and to better understand the long-term prognosis of patients with this rare condition.